Phenotypic and Functional Diversities of Myeloid-Derived Suppressor Cells in Autoimmune Diseases - Huijuan Ma; Chang-Qing Xia (Hindawi Limited, 2018)
Myeloid-derived suppressor cells (MDSCs) are identified as a heterogeneous population of cells with the function to suppress innate as well as adaptive immune responses. The initial studies of MDSCs were primarily focused on the field of animal tumor models or cancer patients. In cancer, MDSCs play the deleterious role to inhibit tumor immunity and to promote tumor development. Over the past few years, an increasing number of studies have investigated the role of MDSCs in autoimmune diseases. The beneficial effects of MDSCs in autoimmunity have been reported by some studies, and thus, immunosuppressive MDSCs may be a novel therapeutic target in autoimmune diseases. There are some controversial findings as well. Many questions such as the activation, differentiation, and suppressive functions of MDSCs and their roles in autoimmune diseases remain unclear. In this review, we have discussed the current understanding of MDSCs in autoimmune diseases.